Peran Badan Usaha Milik Desa (BUM-Des) dalam Meningkatkan Pendapatan Usaha Kecil Menengah (UKM) di Desa Gerung Permai, Kecamatan Suralaga, Kabupaten Lombok Timur - Bahri, Salmi Yuniar; Khalik, Abdul; Romiza, Martin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Small and Medium Enterprises (SMEs) are one of the pillars of the domestic economy, especially for village government. However, they often do not get good support from the village government. Therefore, the government must involve the existence of Village-Owned Enterprises (BUMDes) to increase the income of SMEs so that they can improve the village economy. Village-Owned Enterprises have become a pillar of social economy (social economy) and commercial (commercial Institution) for people who want to manage and develop the potential and needs of villages to be used as business facilities in increasing village community income, as well as contributing to good social service and presentation. Meanwhile, as a commercial institution, it aims to seek profit through offering local resources (goods and services) to the community. This research uses a qualitative descriptive approach that emphasizes understanding the design of the proposed social phenomenon approach from the subject of the research perspective. This research was conducted in Gerung Permai Village, Suralaga District, East Lombok Regency by involving BUMDes Management and UKM actors as sources of data taken by means of interviews and questionnaires. The results of the research are that BUMDes Gerung Permai, Suralaga District, East Lombok Regency supports the existence of SMEs as a means to improve the community's economy. Therefore, BUMDes plays an active role in providing assistance to SMEs in the form of savings and loans with only one percent interest.